A study on customer satisfaction in the training service sector: Saffone Counselling Training and Consultant Sdn Bhd / Noradahwiah Moktar, Noraini Zainuddin and Noor Zaidah Omar - Moktar, Noradawiah; Zainuddin, Noraini; Omar, Noor Zaidah (2016)
Saffone Counselling and Training Consultant (Saffone) provides professional and corporate training programs. The ever expanding training industry in Malaysia requires Saffone to remain competitive to maintain the business and ensure higher return. This research focuses on the study of customer satisfaction in the training sector in Saffone by identifying the current business condition of Saffone, determining the relationship between price, service quality and corporate image towards customer satisfaction. The final objective is to propose a strategic initiatives using Blue Ocean Strategy to improve customer satisfaction and ultimately financial performance for Saffone. The primary data was obtained through an interview with key personnel of Saffone. Quantitative data was obtained through survey conducted where questionnaires were distributed to participants of selected courses. Survey questionnaire was analysed using SPSS and analysis such as correlation and regression were used to compute the data. The finding recommended Saffone to focus on its market penetration and product development. There are strong positive relationship between the Price, Corporate Image and Service Quality, the three variables and customer satisfaction. The Blue Ocean Analysis revealed certain initiatives to be taken to increase customer satisfaction and better allocation of its funds. The suggested increase in price would enable funds to be used elsewhere. Service quality dimensions that do not require funding should be raised whilst those that incurs high costs like empathy should be reduced. Reliability and responsiveness can be improved by staff training and better management both of which require minimal injection of funds. Furthermore, creating a customer data base would further enhance Saffone's performance.